AB0130 THE EFFECTS OF METHOTREXATE ON THE VASCULAR ENDOTHELIUM. (June 2019) - Lang, Marie; Pericleous, Charis; Maughan, Robert; Kiprianos, Allan; Mason, Justin
Abstract : Background: Anti-inflammatory therapy has been recently validated as a treatment option for patients with cardiovascular disease (CVD) [1]. The anti-inflammatory drug methotrexate (MTX) reduces cardiovascular risk in patients with systemic inflammatory rheumatic diseases [2]; possibly by improving endothelial function [3]. However, the molecular basis of the drug's anti-inflammatory and potential anti-atherogenic effects on the vasculature is not well described. Objectives: Our goal was to characterize the actions of MTX on vascular endothelial cells (EC). Methods: MTX-treated human umbilical vein (HUVEC) or aortic endothelial cells (HAEC) were analyzed by quantitative real-time PCR (qRT-PCR), immunoblotting and phospho-kinase activity arrays. EC were treated with tumor necrosis factor (TNF)-α to induce pro-inflammatory activation. EC viability and cell cycle were evaluated by flow cytometry using Annexin V and/or propidium iodide staining. For selected experiments, EC were exposed to laminar (LSS; 20dyn/cm 2 ) or oscillatory shear stress (OSS; 0±5dyn/cm 2, 2Hz) using a parallel plate model. Results: Under static conditions, MTX independently increased the activity of multiple kinases in quiescent and TNFα-activated EC. MTX-activated kinases included the mitogen-activated protein kinase (MAPK) p38 and Akt. MTX did not inhibit TNFα-induced nuclear factor kappa B (NFκB) transcriptional activation, signaling or target gene expression. However, MTX induced pro-inflammatory markers such as vascular cell adhesion molecule (VCAM)-1 in an additive manner with TNFα. Functionally, MTX did not induce apoptosis but caused S-phase cell cycle arrest, which, along with p38 and Akt activation, could be abrogated by supplementation with folinic acid. Findings to date in EC subjected to shear stress are somewhat different. MTX had no or a mild inhibitory effect on kinase signaling in EC under LSS and OSS respectively. MTX did not affect cell proliferation nor baseline or OSS-induced VCAM-1 expression in EC under shear stress. Conclusion: In static EC, low-dose MTX caused cell cycle arrest through folate depletion, which is a known mechanism of action in other cell types. Of note, this response was not seen in EC pre-conditioned by shear stress and emphasizes the impact of biomechanical forces on endothelial phenotype and response to exogenous stimulation. This is the first report to study the effects of MTX on EC under shear stress, which will be crucial in understanding its molecular actions on the vasculature. References: [1] Ridker, P.M., et al., Antiinflammatory Therapy with Canakinumab for Atherosclerotic Disease. N Engl J Med, 2017. 377(12): p.1119-1131. [2] Micha, R., et al., Systematic review and meta-analysis of methotrexate use and risk of cardiovascular disease. Am J Cardiol, 2011. 108(9): p.1362-70. [3] Guin, A., et al., Effects of disease modifying anti-rheumatic drugs on subclinical atherosclerosis and endothelial dysfunction which has been detected in early rheumatoid arthritis: 1-year follow-up study. Semin Arthritis Rheum, 2013. 43(1): p.48-54. Disclosure of Interests: Marie Lang: None declared, Charis Pericleous: None declared, Robert Maughan: None declared, Allan Kiprianos: None declared, Justin Mason Consultant for: Prof Mason has worked as a paid Consultant for Roche/Chugai and Novartis, Speakers bureau: Prof Mason has been a paid speaker for Roche/Chugai